2021
DOI: 10.1101/2021.02.11.21251166
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Superantigenic TCR Vbeta 21.3 signature in Multisystem Inflammatory Syndrome in Children

Abstract: Multiple Inflammatory Syndrome in Children (MIS-C) is the most severe pediatric form of COVID-19 and occurs in previously healthy children. MIS-C combines features of Kawasaki disease and Toxic Shock Syndrome (TSS). We characterized the immunological profile of 27 MIS-C cases in comparison with 4 KD and 4 TSS cases. Similarly to TSS, an increase of serum inflammatory cytokines (IL-6, TNF-a, CD25s) was observed in MIS-C contrasting with low expression of HLA-DR monocytes, a feature often associated with immune … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
4
1
Order By: Relevance
“…Notably, IL6 expression was not increased in this South African cohort compared to healthy controls, despite several prior studies demonstrating elevation of this cytokine in MIS-C (10,17,19,(55)(56)(57)(58)(59)(60)(61) or its association with MIS-C severity (62-66). In fact, although not statistically significant, IL6 expression clustered into clade 1 (Figure 2): genes that appeared downregulated in our cohort compared to healthy controls.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Notably, IL6 expression was not increased in this South African cohort compared to healthy controls, despite several prior studies demonstrating elevation of this cytokine in MIS-C (10,17,19,(55)(56)(57)(58)(59)(60)(61) or its association with MIS-C severity (62-66). In fact, although not statistically significant, IL6 expression clustered into clade 1 (Figure 2): genes that appeared downregulated in our cohort compared to healthy controls.…”
Section: Discussioncontrasting
confidence: 72%
“…MIS-C patients have high serum titres of neutralising IgG SARS-CoV-2 antibodies, suggesting a post-infectious aetiology (2). Although the immunological profile of MIS-C is not yet completely understood, investigations have reported elevated levels of several inflammatory and migratory cytokines, presence of autoantibodies, and immune cell repertoires that could be distinguished from paediatric or adult COVID-19 patients and KD (5,9,(17)(18)(19)(20). Polyclonal TRBV11-2 T cell enrichment suggests superantigen stimulation may underly MIS-C pathogenesis (19,21).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, these results draw parallels to other diseases in which exposure to a new antigen leads to autoimmunity, such as paraneoplastic autoimmune disease or crossreactive viral epitopes between EBV and host proteins in multiple sclerosis (24)(25)(26)31). An expansion of TRVB11-2 T-cells in MIS-C has been shown (23,(36)(37)(38)(39), and while a superantigen has been postulated, it has yet to be identified. Recent studies have shown that tissue resident Tcells exhibit site-specific expansions (59), and that MIS-C patients have a distinct increase in activated circulating T-cells with a tissue-resident phenotype (41), leading to speculation that these T-cells may be driving the TRVB11-2 expansion.…”
Section: Discussionmentioning
confidence: 64%
“…Distinctive T-cell signatures have also been reported in MIS-C, including an expansion of TRVB11-2 T-cells (23,(36)(37)(38)(39) accompanied by autoimmune-associated B-cell expansions (21).…”
Section: Introductionmentioning
confidence: 99%
“…This immune response includes superantigen-like activation of T-cells with expansion of polyclonal expansion of TCR Vbeta 21.3 + CD4 + and CD8 + T-cells, something which is not seen in toxic shock syndrome, Kawasaki disease or COVID-19 in general. In addition, host genetics might alter the susceptibility to develop MIS-C [16][17][18][19][42][43][44].…”
Section: Discussionmentioning
confidence: 99%